Lietuviškų knygų leidėjai ir jų leidiniai 1795–1864 m. - Navickienė, Aušra (Knygotyra, 1993)
1091 Lithuanian books were published in 1795–1864. 585 of them were edited in Great Lithuania. The production of books increased twofold in comparison with the period up to 1795. The circle of Lithuanian books’ publishers had changed in quantity and quality. The Lithuanian books were published not only by traditional publishing houses, printing houses and bookstores but by social institutions, publishing and political organizations, state and science institutions of czarist Russia. Special group was formed by individual publishers. Weil-known Lithuanian democratic cultural workers cherrishing Lithuanian secular books played a great role among them (S. Stanevičius, S. Daukantas and others). M. Akelaitis had organized a fund for Lithuanian books series „Peoples’ library“ publishing. That was a new phenomenon in Lithuanian book publishing institution which renewed the tradition of publishers’ group activities (as earlier the group of Žemaičiai students in Vilnius university, the friends of S. Daukantas in Petersburg. the intelligentsia of Varniai under the leadership of M. Valančius). According to the accumulated data 362 books were published by publishing enterprises, 124 by individual publishers, 94 by various institutions and organizations (the publishers of 8 more books are unknown). The prayerbooks, books of songs extracts from the Bible with commentary of eighteenth century were in great demand. The profit from this business compelled the foreign publishers and booksellers to competition among themselves. The workers of Lithuanian literature were concerned with the edition of first Lithuanian fiction, folklore, history and original educational works. They received aid from secular and church supporters. Russia state institutions publishing activity was limited to some books on law and hygiene and political proclamations (in 1831, 1863–1864). Lithuanian publications were used in political fight for the first time.